2015
DOI: 10.1007/s00420-015-1064-8
|View full text |Cite
|
Sign up to set email alerts
|

Measured by the oxygen uptake in the field, the work of refuse collectors is particularly hard work: Are the limit values for physical endurance workload too low?

Abstract: PurposeCollecting waste is regarded as a benchmark for “particularly heavy” work. This study aims to determine and compare the workload of refuse workers in the field. We examined heart rate (HR) and oxygen uptake as parameters of workload during their daily work. MethodsSixty-five refuse collectors from three task-specific groups (residual and organic waste collection, and street sweeping) of the municipal sanitation department in Hamburg, Germany, were included. Performance was determined by cardiopulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 27 publications
(40 reference statements)
3
24
1
3
Order By: Relevance
“…For example, workers of a municipal sanitation department also reached similar values (averaging 1103 ml/min for a period of 1 h) (Preisser et al 2016b). In this study, the authors found that refuse collection could be classified as heavy work with a high cardiovascular load, based on similar methods of field HR and measurements.…”
Section: Discussionmentioning
confidence: 87%
“…For example, workers of a municipal sanitation department also reached similar values (averaging 1103 ml/min for a period of 1 h) (Preisser et al 2016b). In this study, the authors found that refuse collection could be classified as heavy work with a high cardiovascular load, based on similar methods of field HR and measurements.…”
Section: Discussionmentioning
confidence: 87%
“…Der hier beschriebene Zeitrahmen von 45 bis 60 Minuten war tolerabel, eine Messung über eine ganze Arbeitsschicht (8 Stunden) wäre dies aber nicht. Die Probanden aus der Studie "Müllwerker in Hamburg" (siehe[17]) tolerierten klaglos die Maske und Sensorik bis zu 90 Minuten.Sicher ist diese Methode nicht für alle denkbaren Arbeitsbereiche anwendbar, so z. B. nicht für Personen, die bei der Arbeit kommunizieren müssen (Verkaufspersonal, Ärzte in der Praxis mit sprechender Medizin u.…”
unclassified
“…Zur Beurteilung der konkreten Arbeitsbelastung im Beruf mit Bestimmung der V O 2 ist die mobile Spiroergometrie geeignet. So kann die kardiopulmonale Belastung während der Arbeit hierüber detailliert erfasst werden [306].…”
Section: Berufliche Leistungsfähigkeit -Bestimmung Der Dauerleistungsunclassified
“…Nach bisherigen Studien und Vorgaben wird empfohlen, dass der O 2 -Verbrauch 30 -35 % der V O 2 max bei einem Arbeitsumfang von 480 Minuten nicht überschreiten sollte [307 -309]. Neuere Daten zeigen, dass auch Dauerbelastungen von 35 -50 % der individuellen V O 2 toleriert werden [160,306,310]. Bei ausreichenden Pausen oder kürzeren Arbeitszeiten kann ein Grenzwert von 45 % der V O 2 max toleriert werden [311].…”
Section: Berufliche Leistungsfähigkeit -Bestimmung Der Dauerleistungsunclassified